FAKTOR-FAKTOR YANG MEMPENGARUHI KEBERLANJUTAN USAHA KELUARGA STUDI PADA USAHA KELUARGA MULTI ETNIS DI KECAMATAN KOTA WAINGAPU) - Ridho, Muhammad Ali; Situmorang, Tumpal P (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This research aims to determine the principles of community participation in infrastructure development planning in Sipodeceng Village, Baranti District, Sidenreng Rappang Regency. The population in this study was 3,713 people in Sipodeceng Village, while the sample in this study was 98 people determined using the Slovin formula..This type of research is descriptive research with a quantitative research design. Data collection techniques were carried out through observation, interviews and questionnaires. The data analysis technique used was descriptive analysis, data quality testing and simple linear regression and hypothesis testing using the SPSS version 16 program. The research results showed that, the research results showed that community participation in infrastructure development planning with 6 indicators (thoughts, energy, thoughts and energy, skills, goods and money). which has an average percentage value of 71%. or can be categorized as